HUBUNGAN ANTAR LEMBAGA NEGARA DALAM SISTEM KETATANEGARAAN INDONESIA - Thaher, Irmanjaya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The Indonesian constitutional system regulates the organization and distribution of state power through the trias politica principle, which divides power into executive, legislative, and judicial branches, with a checks and balances mechanism to prevent abuse of power and maintain constitutional democracy. This study analyzes the constitutional framework of the institutional hierarchy, identifies challenges to the implementation of checks and balances, including executive dominance and institutional politicization, evaluates the role of the Constitutional Court as the guardian of the constitution, examines the dynamics of central-regional relations, and formulates reform recommendations to strengthen the balance of power and democratic governance. The research methodology employed a Systematic Literature Review (SLR) conducted in a systematic and structured manner to identify, evaluate, and synthesize relevant scholarly articles to generate a comprehensive, evidence-based understanding of conceptual developments and empirical findings. The results show that the 1945 Constitution establishes a clear institutional hierarchy based on the trias politica. However, the implementation of checks and balances faces challenges such as executive dominance, weakening of the legislative-judicial system, and institutional politicization, which undermine the quality of governance. The Constitutional Court plays a strategic role in resolving conflicts of authority and strengthening constitutional supremacy through judicial review and authoritative constitutional interpretation. The conclusion emphasizes the need for systemic reform to strengthen checks and balances, increase the independence of state institutions, and create a balance between decentralized regional autonomy and unity of command in maintaining the integrity of the unitary state government. This research provides theoretical contributions to the development of constitutional law and practical contributions to the formulation of policies to strengthen Indonesia’s accountable and democratic constitutional system.